Microscopic characteristics of the inferior tarsal muscle and its surroundings in Korean - Park, Jung Min (International Journal of Ophthalmology Press, 2013)
AIM: To investigate the detailed microscopic anatomic structures of the lower eyelid in Korean cadavers. METHODS: Eight lower eyelids of 4 formalin-fixed Asian cadavers (4 males; age range, 48-69 years; mean age, 60.2 years) were examined. Three perpendicular dissected sections with a 2mm thickness were obtained from each eyelid to investigate anatomic shapes, size and relationship with surrounding structures. One section was obtained from the midline and 2 the other sections were obtained from a 3mm apart from the lateral and medial tarsus margins. RESULTS: The inferior tarsal muscle fibers were not directly attached to the tarsus but were only linked to the tarsus with enclosed fibrous fascia. The inferior tarsal muscles connected loosely with the capsulopalpebral fascia anteriorly and the conjunctiva posteriorly. The inferior tarsal muscle runs horizontally to the tarsus according to the shape of muscle fibers. The capsulopalpebral fascia consisted of an anterior and posterior layer. The anterior layer reached the orbital septum and subcutaneous fat but the posterior layer forwarded into the tarsus. Lockwood's ligament was separated from the inferior tarsal muscle and capsulopalpebral fascia or fused into the capsulopalpebral fascia. CONCLUSION: This study suggests that the inferior tarsal muscle which runs horizontally and doesn't insert directly into the tarsus, plays an important role in the movement and localization of the lower eyelid.